Upper and Lower Solution Method for Fourth-Order Four-Point Boundary Value Problem on Time Scales - Ilkay Yaslan Karaca (Abstract and Applied Analysis)
We consider a fourth-order four-point boundary value problem for dynamic equations on time scales. By the upper and lower solution method, some results on the existence of solutions of the fourth-order four-point boundary value problem on time scales are obtained. An example is also included to illustrate our results.